Die Griekse manuskrip van die Kindheidsevangelie van Tomas in Kodeks Sinaïtikus (Gr 453) vertaal in Afrikaans - Aarde, Andries van (HTS teologiese studies, 2005)
The Greek manuscript of the Infancy Gospel of Thomas in Codex Sinaiticus (Gr 453) translated into AfrikaansFourteen Greek manuscripts and early translations exist of the Infancy Gospel of Thomas. The Greek version in Codex Sinaiticus (Gr 453) represents the most authentic version. The article shows that the reproduction of this Greek manuscript was made possible because of Constantin von Tischendorf’s collection of Greek manuscripts and a Latin translation. The aim of this article is to provide an Afrikaans translation of the Greek manuscript in Codex Sinaiticus (Gr 453) in order to purport further investigation into the redactional tendencies found in the manuscript. These tendencies are oriented by motifs in the Ebionite Gospels rather than in Gnosticism.